Overview of Device-to-Device Communication and Vehicle-to-Vehicle Communication - Srikanth Kamath, H.; ., Sreelakshmi; Siri Chandana Reddy, Muthyala; Camilo Monteiro, Chelsea (International Journal of Engineering and Technology, 2018)
5G (5th generation mobile networks or 5th generation wireless systems) is the next major phase of mobile telecommunications standards beyond the current 4G LTE (Long-Term Evolution) standards. 5G technology needs to be specified, developed, and deployed by a variety of industry players including network equipment vendors, network operators, semiconductor vendors, and device manufacturers. The scope of 5G will range from mobile phones to next-generation automobiles. Device to Device (D2D) Communication is regarded as a promising technology in 5G to provide low power, high data rate and low latency. Introducing D2D poses many challenges and risks to the longstanding cellular architecture, which is centred on the base station.Â